Contribution to the knowledge on the genus Barsine Walker, 1854 from mainland China and Indochina, with description of a new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Huang, Si-Yao; Volynkin, Anton V.; Černý, Karel; Wang, Min; Fan, Xiao-Ling (Zootaxa, 2019)
A new species of the genus Barsine, viz. Barsine fangchenglaiae Huang, Volynkin, Černý & Wang sp. nov. from SW China, N Thailand and N Vietnam is described. The following six taxa are confirmed as new records to China: B. pretiosa Moore, 1879, B. defecta defecta Walker, 1854, B. gratissima (de Joannis, 1930), B. flammealis Moore, 1878, B. mactans Butler, 1877 and Barsine vinhphucensis Spitsyn et al., 2018. The new synonymy is established: Barsine pretiosa Moore, 1879 = Barsine pseudomactans Volynkin & Černý, 2016, syn. nov. Adults and genitalia of all species aforementioned are illustrated.